A systematic literature review on the effectiveness of lycopene and probiotics in eradicating the Helicobacter pylori causing gastritis - Padmanabhan, Kousalya; Rahim, Muhamad Hafiz; Rukayadi, Yaya; Zawawi, Norhasnida; Chong, Kah Hui; Mohammad Sabri, Nur Shahera; Jiang, Shan; Abdul Jabar, Nor Azmiraah; Nor-Khaizura, Mahmud Ab Rashid (SAGE Publications Ltd, 2025)
Background: Gastritis, caused by Helicobacter pylori, is a major health concern affecting nearly half of the global population and is linked to severe gastrointestinal diseases, including gastric cancer. Despite available treatments, increasing antibiotic resistance raises the risk of treatment failure, highlighting the need for alternative therapies. Probiotics and antioxidants, such as lycopene, have shown promise in managing H. pylori-related gastric diseases. Aim: This study conducts a systematic literature review (SLR) to evaluate the potential of lycopene, enhanced through lactic acid bacteria (LAB) fermentation of plant-based sources, in treating H. pylori-induced gastritis. Methodology: Using the PRISMA method, articles from Google Scholar, Science Direct, and PubMed (2018–2025) were reviewed. Out of 279 papers analyzed, 30 met the inclusion criteria, focusing on lycopene production via LAB fermentation and its efficacy against H. pylori. Results: Findings indicate that LAB fermentation enhances lycopene's bioavailability and stability, while certain LAB strains exhibit inhibitory effects on H. pylori growth. Lycopene demonstrates anti-carcinogenic properties, reducing oxidative stress and inflammation in gastric cells without harming normal epithelial cells. However, its effectiveness varies depending on fermentation conditions and bacterial strains. Conclusion: This study underscores the potential of combining probiotics and lycopene as an adjunct therapy for H. pylori infections, particularly amid antibiotic resistance. Future research should optimize fermentation processes, identify the most effective LAB strains, and conduct clinical trials to validate fermented lycopene's therapeutic potential. This approach could offer a sustainable and effective alternative to conventional antibiotic treatments.